On the maximum angle condition for the conforming longest-edge n-section algorithm for large values of n - Korotov, Sergey; Plaza, Ángel; Suárez, José P. (Computer aided geometric design, 2015)
In this note we introduce the conforming longest-edge n-section algorithm and show that for n≥4 it produces a family of triangulations which does not satisfy the maximum angle condition.